Follow the rabbit: Field Guide to Systemic Design - CoLab (Government of Alberta, 2018)
This Field Guide is designed to support budding systemic designers to facilitate and lead systemic design projects. It’s designed for system ic designers who have basic familiarity with SD concepts and are looki ng for some practical tips and tools to put theory into action. While this Guide was designed with Government of Alberta staff in mind, the content applies across a range of issue areas, sectors, and intersecti ons. The Guide goes through a systemic design project from concept to implementation. It takes you through the workshop planning process, an d discusses workshop roles and client relations. In the FAQs, you’ll f ind explanations to some commonly asked questions about systemic desig n concepts to help you introduce others to SD and bring them along wit h you. You’ll get the most out of this field guide if you approach it with a systemic design mindset – open, willing to try things, a desire to learn, and a ‘yes, and’ orientation. Think of this field guide as an early stop in your systemic design journey: it’s not the end of you r learning – it’s a jumping off point. In the Additional Resources sec tion, you can connect to more in-depth explorations of concepts and pr actical applications.